PENGARUH PENCAMPURAN DUA JENIS AGREGAT KASAR TERHADAP KUAT TEKAN BETON - Agustin Gunawan (Universitas Bengkulu, 2019)
This research aims to find out influence of two combined coarse aggregate toward concrete compressive strength. Two kinds of aggregate which have different quality gradation are coarse aggregate from Quarry Sukaraja (KS) and Pondok Kubang (KP). Conceret mix design used a composition of 1 cement : 2 sand : 3 coral with two coral variations(50% KS + 50% KP and 35% KS + 65% KP), and two kinds of sand (river sand and sea sand). The sample was cylindrical form with diameter of 15 cm, and height of 30 cm as many as 32 samples. Compressive strength test was done at 28 days. Test results of concrete compressive strength showed that 50% KS + 50% KP can improve value of concrete compressive strength to normalconcrete (KS) (16,76% (for river sand) and 17,98% (for sea sand)). Concrete compressive strength of mixture of 50% KS + 50% KP increased 31.9% (for river sand) and 30% (for sea sand) to the normal concrete (KP). By a mixture of 35% KS + 65% KP, concrete compressivestrength increased 6,22% (for river sand) and 15,97% (for sea sand) to normal concrete (KS), and a mixture of 35% KS + 65% K increased concrete compressive strength 20% (for sand river) and 27,78% (for sea sand) to normal concrete (KP).